IMPROVING MATHEMATICS LEARNING OUTCOMES WITH CTL ASSISTED BY BEADS MEDIA - Yupika Anggraini (CV Grasta Glory, 2026)
Background: Low mathematics learning outcomes and students’ difficulties in understanding abstract concepts remain a common problem in elementary schools. Conventional teaching methods often fail to connect mathematical content with students’ real-life experiences, resulting in low engagement and achievement. Therefore, innovative learning models and concrete media are needed to improve students’ conceptual understanding. This study aims to determine whether the Contextual Teaching and Learning (CTL) model assisted by beads media can improve mathematics learning outcomes of fifth-grade elementary school students. This study employed Classroom Action Research (CAR) involving 20 fifth-grade students of SD Negeri 46 Lubuklinggau. Data were collected through observation, documentation, and achievement tests, and analyzed using descriptive quantitative techniques. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. In Cycle I, the pre-test results showed 15% of students in the very low category, while post-test results increased to 75% in the moderate category. In the second meeting of Cycle I, student achievement reached 30%. In Cycle II, the pre-test results increased to 40% (low category), and the post-test results significantly improved to 85% in the very high category. These findings indicate a substantial improvement in students’ mathematics learning outcomes after the implementation of CTL assisted by beads media.The application of the CTL model assisted by beads media effectively improves elementary students’ mathematics learning outcomes and conceptual understanding. study recommends the use of CTL combined with concrete learning media in mathematics instruction and suggests further research involving larger samples and different mathematical topics.